India’s Digital Health Transformation: Advancements and Challenges in Telemedicine - Sinha, Nupur; Rahul, Rahul (Jurnal Kebidanan Manna, 2024)
Telemedicine refers to the use of telecommunications technology to diagnose and treat patients remotely, giving low-income areas access to high-quality healthcare. The first documented instance of telemedicine dates back to the early part of the 1900s, at which time an ECG was sent over a phone line. Telemedicine has advanced significantly in terms of technology and healthcare delivery since then. NASA and ISRO had a significant part in this. The establishment of the National Telemedicine Taskforce in 2005 by the Indian Health Ministry cleared the path for the accomplishment of several initiatives, including the ICMR-AROGYASREE, NeHA and VRCs. Family doctors benefit from telemedicine by having easy access to specialists and assistance in patient monitoring. Around the world, different telemedicine systems, such as store and forward, real-time, remote or self-monitoring, offer a range of educational, disease screening, disaster management and healthcare delivery and management services. Telemedicine may undoubtedly lessen the strain on the healthcare system to a significant level, even though it cannot solve every issue. Telemedicine has reshaped healthcare delivery, particularly for rural populations. By reducing travel, broadening access to specialists, supporting chronic disease management, and addressing professional shortages, it offers a promising solution to healthcare disparities. However, challenges like infrastructure limitations and technology literacy need ongoing attention to ensure equitable, long-term access for all.